PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MADRASAH TSANAWIYAH NURUL FALAH AIRMOLEK - Usman; Nur Soleh; Fatima Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students’ learning activeness in Akidah Akhlak lessons, which is reflected in limited participation during discussions, lack of confidence in expressing opinions, and the dominance of teacher centered instruction. One instructional alternative considered effective in improving students’ activeness is the cooperative learning model of the Numbered Head Together (NHT) type. The purpose of this research is to examine the effect of implementing the NHT model on the learning activeness of eighth grade students at Madrasah Tsanawiyah Nurul Falah Air Molek. This research employed a quantitative approach using a quasi experimental method with a pretest posttest control group design. The research subjects consisted of class VIII as the experimental group and another class as the control group. Data were collected through observation sheets, learning activeness questionnaires, and documentation, and were analyzed using descriptive and inferential statistical tests. The findings indicate a significant increase in students’ learning activeness in the class taught using the NHT model compared to the class receiving conventional instruction. Therefore, it can be concluded that the cooperative learning model of the NHT type has a positive effect on students’ learning activeness in Akidah Akhlak instruction.